The liberation of Jerusalem (Gerusalemme liberata) - Tasso, Torquato, 1544-1595 (Oxford world's classics (Oxford University Press), 2009)
Tasso's epic poem concerns the capture of Jerusalem by the Crusaders in 1099, and combines the theme of war with romantic and magical tales of love between pagan and Christian. This is the first modern translation that faithfully reflects the sense and verse form of Tasso's hugely infuential masterpiece. - ;'The bitter tragedy of human life-- horrors of death, attack, retreat, advance, and the great game of Destiny and Chance. ' In The Liberation of Jerusalem (Gerusalemme liberata, 1581), Torquato Tasso set out to write an epic to rival the Iliad and the Aeneid. Unlike his predecessors, he too.